ANALISIS KINERJA PEGAWAI PADA DINAS TENAGA KERJA, TRANSMIGRASI DAN KEPENDUDUKAN PROVINSI JAWA TENGAH - Maharani, Andika; Warsono, Hardi; Mustam, Mochamad (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Low quality performance of employees at Departement of Manpower, Transmigration and Population of Central Java Province had motivated the author to implement a study of “Analysis of Staff Performance at Departement of Manpower, Transmigration and Population of Central Java Province. This study, analysis of staff performance at Departement of Manpower, Transmigration and Population of Central Java Province, was implemented as a result of low quality staff performance found in the office. The main problem of the study was lacking work capability, motivation and work discipline. This study aimed to test the effects of each independent variable: work capability, motivation, and work discipline, on staff performance. Data were obtained from an observation method according to field conditions as well as from questionnair dissemination to the study respondents. Analysis instrument used was coefficient correlation using an SPSS version 16.0. The study resulted in a positive and significant relationship between the independent variables (work capability, motivation, and work discipline) on staff work performance at Departement of Manpower, Transmigration and Population of Central Java Province the scales of 0,295 (work capability), 0,750 (motivation), and (work discipline) 0,499. In addition, collective significance rate of the relationship between the three variables and the staff performance was 52,5% Keywords: